2021
DOI: 10.1002/vms3.488
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of antimicrobial action of aloe vera and antibiotics against different bacterial isolates from skin infection

Abstract: Aloe vera is reputed to have medicinal properties. For centuries, it has been used for an array of ailments such as mild fever, wounds and burns, gastrointestinal disorders, diabetes, sexual vitality and fertility problems to cancer, immune modulation, AIDS and various skin infections. In present study, antibacterial activity of aloe vera gel extracts was tested against some common skin infection pathogens, that is, Escherichia coli, Shigella, Salmonella spp. and Staphylococcus aureus all were recorded positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
3
14
1
2
Order By: Relevance
“…Aloe vera root and leaf ethanol extracts exhibited good antibacterial activity with a zone of inhibition of > 13 mm at a concentration of 30 mg[ 83 ]. Arbab et al [ 84 ] also concluded that ethanol extracts are more efficacious than conventional extracts. Antifungal activity was noted against Fusarium and Aspergillus [ 83 ].…”
Section: Aloe Veramentioning
confidence: 99%
“…Aloe vera root and leaf ethanol extracts exhibited good antibacterial activity with a zone of inhibition of > 13 mm at a concentration of 30 mg[ 83 ]. Arbab et al [ 84 ] also concluded that ethanol extracts are more efficacious than conventional extracts. Antifungal activity was noted against Fusarium and Aspergillus [ 83 ].…”
Section: Aloe Veramentioning
confidence: 99%
“…Bacterial resistance to antibiotics is increasingly becoming a concern to animal health. Currently used antibiotic agents fail to end many bacterial infections due to super‐resistant strains (Arbab et al., 2021d). The use and misuse of antimicrobial drugs accelerate the emergence of drug‐resistant strains.…”
Section: Antibiotic Resistance In E Colimentioning
confidence: 99%
“…compared to a prior study (Safia Arbab et al, 2021) that was carried out in China. Our current investigation revealed stronger antioxidant and greater germicide activeness than standard ones, contrary to the earlier study which claimed that the bioactive components of Aloe vera had less antioxidant and antimicrobial effects than standard antioxidants and antimicrobial agents.…”
Section: Comparison With the Previous Studymentioning
confidence: 99%
“…(IV) Bacteria actively export medicine via the employment of a multi-drug resistance pump (Metting Patricia J, 2019). The multidrug resistance pump imports protons and, in an exchangekind reaction, exports a lot of overseas molecules such as quinolones antibiotics( Safia Arbab et al, 2021). In the present study, we aimed toward looking for a new natural Aloe vera herb augmenting antimicrobial and antioxidant activities to defend in opposition to distinctive deadly infections and to avert carcinogenicity thru minimizing DNA harm via way of means of dangerous oxidizing agents consisting of gamma radiation and others.…”
Section: Introductionmentioning
confidence: 99%